ANALISIS PARTISIPASI MASYARAKAT DI WILAYAH SATELIT DALAM PEMBANGUNAN DAN PEMELIHARAAN DRAINASE - Nana Diana; R. Hamdani Harahap; Muryanto Amin (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2020)
This study aims to see the community participation in the satellite area in the construction and maintenance of Drainage in the Village Marindal II District Patumbak Deli Serdang. The research method used to answer the problem in this research is the method of qualitative research approach. Data obtained through in-depth interviews, literature study and documentation. Informant research comes from the elements of sub-district government and community. The results of the research show that the participation, involvement and utilization of drainage facilities are running well